Financial Literacy, Economic Preferences, and Adolescents' Field Behavior - Michael Razen; Jürgen Huber; Laura Hueber; Michael Kirchler; Matthias Stefan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Financial literacy and economic preferences are considered to be important drivers of health, income, and general well-being. We bridge the gap between studies on financial literacy and research on economic preferences by investigating how they interplay with each other and with the field behavior of adolescents. First, we report that financial literacy scores are positively associated with patience, male gender, and educational level of the father. Second, we observe that risky field behavior like smoking and gambling is positively associated with various measures of risk-tolerance, and negatively associated with patience. Finally, we discuss implications for financial education programs.
Keywords: C93; D91; D81; G53; J13; 330; Experimental finance; financial literacy; time preferences; risk preferences; adolescents